In vivo antitumor activity of by-products of Passiflora edulis f. flavicarpa Deg. Rich in medium and long chain fatty acids evaluated through oxidative stress markers, cell cycle arrest and apoptosis induction. (August 2018) - Mota, Nádia S.R.S.; Kviecinski, Maicon R.; Zeferino, Rodrigo C.; de Oliveira, Daniela A.; Bretanha, Lizandra C.; Ferreira, Sandra R.S.; Micke, Gustavo A.; Filho, Danilo Wilhelm; Pedrosa, Rozangela C.; Ourique, Fabiana
Abstract: Antiinflammatory and antitumor activity has been reported in Passiflora edulis (yellow passion fruit) nevertheless the intrinsic mechanisms of action are not fully elucidated. The present study aimeds to perform a comparison between the antitumor activity involving the crude extract (HCE) and the supercritical fluid extract with ethanol as co-solvent (SFEtOH) from P. edulis f. flavicarpa Deg. The in vitro cytotoxicity was evaluated in MCF-7 cells, while the in vivo antitumor activity was assessed in male Balb/c mice inoculated with Ehrlich carcinoma cells. SFEtOH exhibited higher antitumor activity compared to HCE. Wherein, SFEtOH showed an EC50 of 264.6 μg/mL against MCF-7 cells as well as an increased inhibition of tumor growth of 48.5% (p < 0.001) in male Balb/c mice, thereby promoting an increased mice lifespan to approximately 42%. Moreover, SFEtOH caused lipid (p < 0.001) and protein (p < 0.001) oxidation by increasing glutathione redox cycle activity while decreased the thioredoxin reductase activity (p < 0.001). SFEtOH also induced oxidative DNA damage in Ehrlich ascites carcinoma (EAC) cells leading to G2/M cycle arrest and has increased apoptotic cells up to 48.2%. These data suggest that the probable mechanisms of antitumor effect are associated to the lipid, protein and DNA damage, leading to cell cycle arrest and triggering apoptosis via mitochondrial pathway, should be probable due to the presence of medium and long chain fatty acids such as lauric acid.